Developing Students' Public Speaking Skills through the Mind Mapping Strategy: A Classroom Action Research - Taufik Hidayat; Rina Agustini; Selvia Salwa Firdausi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This study aimed to describe the implementation of the Mind Mapping Strategy in developing students' public speaking skills. Public speaking is an essential competency in language learning; however, many students continue to experience difficulties in organizing ideas, delivering speeches coherently, and speaking with confidence. Previous studies have primarily employed mind mapping as a note-taking technique or as a strategy for improving general speaking skills, whereas its use as a pedagogical strategy specifically designed for public speaking instruction remains underexplored. The novelty of this study lies in positioning the Mind Mapping Strategy as a structured pedagogical approach for developing public speaking competence within Classroom Action Research rather than merely as a visual note-taking tool. This study employed Classroom Action Research based on the Kemmis and McTaggart model, conducted over two cycles involving 18 ninth-grade students at SMP Al-Ittihad Jamanis. Data were collected through classroom observations, performance assessments, documentation, and field notes and were analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of the Mind Mapping Strategy significantly improved students' public speaking skills, as reflected in the increase in the mean score from 58.8 in the pre-cycle to 67.4 in Cycle I and 93.9 in Cycle II. Learning mastery also increased from 38.9% to 61.1%, reaching 100% in Cycle II. Improvements were consistently observed across multiple performance aspects, including idea organization, speech fluency, word choice, content mastery, intonation, and self-confidence. Theoretically, these findings provide empirical evidence that mind mapping functions not only as a cognitive organizer but also as an effective pedagogical strategy for enhancing public speaking performance. Practically, the findings offer teachers an accessible and systematic instructional approach for fostering students' communication competence in language classrooms. Overall, this study contributes to the advancement of public speaking pedagogy by demonstrating the broader educational potential of the Mind Mapping Strategy for improving oral communication skills across diverse learning contexts beyond the immediate classroom setting.